Thermomechanical evaluation of new geopolymer binder from demolition waste and ignimbrite slits for application in the construction industry - Mayta-Ponce D.L. (2019)
Geopolymeric mortars with volumetric fractions of 0.6:1:0.3 for a binder powder, fine sand and sodium hydroxide solution (12M), respectively; have been fabricated by mixing the solid materials and the subsequent addition of sodium hydroxide solution 12M to form a workable paste, to later be cured for 28 days at room temperature. The microstructures of the fabricated materials reveal the existence of two phases with notable difference, one continuous to the geopolymer binder phase and another discontinuous of fine sand particles agglutinated by the binder phase. Mechanical compression tests are performed at a constant compression rate of 0.05 mm/min and at temperatures ranged from room temperature to 500°C. The mechanical results are ranged from 19 and 69 MPa for all the materials studied. On the other hand, there was an increase in mechanical resistance up to test temperatures of 200°C and the progressive reduction of resistance at temperatures above 200°C, with a fragile-ductile transition zone between 400 and 500°C and completely ductile behavior from test temperatures of 500°C. © Materials Research Society 2019.